Dynamic risk assesment for driver response in passing over obstacles - Yakut, Oğuz; Eren, Haluk; Kaya, Mustafa; Öksüztepe, Eyyüp; Polat, Mehmet; Omaç, Zeki; Bekler, Derya; Kürüm, Hasan; Çelenk, Mehmet (My University, 2013)
In the urban areas, drivers may need to step over obstacles for safety caution. At this stage, drivers have to slow down and move at low speed while passing over curbs. If there is an obstacle in front or back of the car, driver should step on the gas to speed up the car from zero to cautionary speed to pass over it. The obstacle in question could be curbs, bumper or rim over urban areas. In this scenario, we consider a particular obstacle, namely, a curb. Hence, the driver has to climb over the curb by stepping on the gas, which, in turn, creates a critical driving situation emerging risky move contemplating the car driven or pedestrians as well as obstacles around the car. In this work, depending on response time of driver, while car crosses over obstacle, lateral distance of car taken unintentionally have been estimated. Considering this distance, emerging risk by the situation has been investigated along with influence of height on risk severity experimentation. Relationship among response time of driver, obstacle height and unintentional moving backward distance is determined and presented as a parametric response or outcome function. The study is extended further for modeling unintentional driving behavior in passing over obstacle risk assessment. Subsequently, the undertaken research has enabled us to deduce compensation between the driver response, steep level and geometry of the curb. Furthermore, we give an assessment for estimating the risk causing of the driver response in passing over curb.
Bildiri - Yayımlanmamış
Keywords: Safe parking; Curbs; Low speed accident; Obstacle models; Car torque; Driver response time